PERAN OTORITAS JASA KEUANGAN (OJK) DALAM MENGATASI KEJAHATAN DIGITAL STUDI KASUS KEBOCORAN DATA PADA BANK SYARIAH INDONESIA - HUSAIN, NARTY (Ganec Swara, 2025)
The role of the Financial Services Authority (OJK) in overcoming digital crime, especially related to data leaks at Bank Syariah Indonesia (BSI), is crucial in the current era of digitalization. The case of data leakage that occurred at BSI, where around 1.5 TB of customer data was stolen by a hacker group, showed a discrepancy from the bank that could potentially harm customers. This research aims to analyze OJK’s role and authority in providing legal protection for affected customers, as well as assessing the effectiveness of existing regulations.OJK has the authority to supervise, investigate, and impose sanctions on violations committed by financial institutions, including in terms of protecting customers’ personal data. The legal basis for customer data protection is set out in the Banking Law and OJK Regulation No. 1/POJK.07/2013. In addition, OJK also plays a role in improving public financial literacy to reduce the risk of digital crime. In this context, collaboration between OJK and other institutions, including ministries and law enforcement, is key in combating increasingly complex digital financial crimes.The results show that although regulations are in place, there are still challenges in their implementation, especially in public awareness of the importance of personal data security. Therefore, continuous efforts in education and supervision are needed to ensure effective protection for Islamic bank customers in Indonesia.